If EC bisects ∠BED, then ∠BEC and ∠CED have the same measurement.
∠BEC = ∠CED
From the equation above, find the value of x so we could calculate the measurement of ∠BED
∠BEC = ∠CED
11x + 2 = 8x + 20
Move the one with variable to the left side, and move the constant to the right side
11x + 2 = 8x + 20
11x - 8x = 20 - 2
3x = 18
x = 18/3
x = 6
The value of x is 6
Find the measurement of ∠BED
∠BED is formed by ∠BEC and ∠CED
∠BED = ∠BEC + ∠CED
∠BED = 11x + 2 + 8x + 20
∠BED = 19x + 22
Now input the value of x
∠BED = 19(6) + 22
∠BED = 114 + 22
∠BED = 136
The measurement of ∠BED is 136°. The answer is option d.